2008
DOI: 10.1590/s0103-166x2008000400005
|View full text |Cite
|
Sign up to set email alerts
|

Bem-estar subjetivo emocional e coping em adultos de baixa renda de ambientes urbano e rural

Abstract: Este estudo objetivou avaliar o bem-estar subjetivo emocional e identificar a principal estratégia de enfrentamento (coping) utilizada por indivíduos de baixa renda, com idade adulta avançada (entre 40 e 55 anos), dos ambientes urbano e rural da Paraíba. Considerou-se uma amostra não-probabilística por cotas, distribuídas por ambientes (rural e urbano) e por sexo. Participaram 280 indivíduos, com idade média de 46 anos. Os instrumentos foram: adaptação do Questionário de Saúde Geral, escala de coping e dados b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
0
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
3
0
0
3
Order By: Relevance
“…Such factors are also reported by Albuquerque, Martins, and Neves (2008), in a study on well-being in rural and urban contexts. They point out that despite the rural context, in recent decades, no longer being exclusively agrarian it is still associated with being a pleasant and healthy place to live, where interpersonal relationships are closer and lasting, thus favoring a greater emotional stability and an improvement of personal well-being.…”
Section: Discussionsupporting
confidence: 59%
“…Such factors are also reported by Albuquerque, Martins, and Neves (2008), in a study on well-being in rural and urban contexts. They point out that despite the rural context, in recent decades, no longer being exclusively agrarian it is still associated with being a pleasant and healthy place to live, where interpersonal relationships are closer and lasting, thus favoring a greater emotional stability and an improvement of personal well-being.…”
Section: Discussionsupporting
confidence: 59%
“…Studies with Brazilian samples that analyzed the relationship between low family income and coping strategies revealed that individuals from low-income families have a greater capacity to use coping strategies, since they already deal with poor socioeconomic conditions as the main stressor. Brazilian studies show that patients use more direct strategies, acting and seeking change with greater capacity to adapt to new situations and directly facing problems, as found in the present study (Albuquerque et al, 2008;Nepomuceno et al, 2016).…”
Section: Article In Presssupporting
confidence: 74%
“…Studies have shown effective results of educational, psychosocial, and psychoeducational interventions to prevent and reduce caregiver burden (França et al, 2020). More effective coping strategies have been associated with greater physical QOL, as evidenced in the literature and in the present study (Albuquerque et al, 2008;Muliira et al, 2019). However, coping strategies did not contribute to physical QOL, suggesting their importance on caregives' psychological rather than physical symptoms, impacting therefore mental QOL.…”
Section: Article In Presssupporting
confidence: 68%
“…O primeiro tipo tende a ter o "locus de controle interno" e o segundo o "locus de controle externo(Robbins, 2005).O locus de controle é a crença que uma pessoa possui de poder ou não controlar os eventos de sua vida. Sendo assim, pode ser entendido como uma expectativa generalizada de controle acerca de uma situação ou ação e de seus resultados(Castillo & Ramirez, 2000;Albuquerque, Noriega, Martins & Neves, 2008).Mindfulness ou consciência plena é um tema ainda pouco explorado, sobretudo no Brasil e em contextos organizacionais. Entretanto, têm sido amplamente destacados os benefícios que a consciência plena traz para a saúde, qualidade de vida e bem estar de indivíduos e grupos nos mais diferentes contextos.…”
unclassified